1997
DOI: 10.4319/lo.1997.42.5_part_2.1203
|View full text |Cite
|
Sign up to set email alerts
|

Toxic marine phytoplankton, zooplankton grazers, and pelagic food webs

Abstract: Interactions between toxic phytoplankton and their zooplankton grazers are complex. Some zooplanktcrs ingest some toxic phytoplankters with no apparent harm, whereas others are deleteriously affected. Phycotoxins vary in their modes of action, levels of toxicity and solubility, and affect grazers in different ways. Beyond effects on direct grazers, toxins may accumulate in and be transfcrrcd through marine food webs, affecting consumers at higher trophic levels, including fish, scabirds, and marine mammals. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
265
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(276 citation statements)
references
References 87 publications
4
265
1
2
Order By: Relevance
“…The chemical structures of this group of toxins, including saxitoxin (STX) and approximately 57 derivatives, are well described from the genus and from seafood (Munday, 2014). Paralytic shellfish toxins are sodium-ion channel blockers that can cause potent neurotoxic syndromes in humans as well as fish, seabirds and marine mammals (Cembella, 1998;Turner and Tester, 1997;Turner, 2014). Reported effects on copepods offered PST-containing Alexandrium spp., however, range from none to adverse effects on ingestion rate, egg production, egg hatching and offspring development duration (Dutz, 1998;Frangopulos et al, 2000;Guisande et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of this group of toxins, including saxitoxin (STX) and approximately 57 derivatives, are well described from the genus and from seafood (Munday, 2014). Paralytic shellfish toxins are sodium-ion channel blockers that can cause potent neurotoxic syndromes in humans as well as fish, seabirds and marine mammals (Cembella, 1998;Turner and Tester, 1997;Turner, 2014). Reported effects on copepods offered PST-containing Alexandrium spp., however, range from none to adverse effects on ingestion rate, egg production, egg hatching and offspring development duration (Dutz, 1998;Frangopulos et al, 2000;Guisande et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these rates are difficult to quantify with measurements. Grazing losses inflicted on A. fundyense are a complex function of both the heterotrophic and autotrophic communities (Teegarden and Cembella, 1996;Turner and Tester, 1997;Campbell et al, submitted;Turner and Borkman, submitted). In the absence of observations sufficient to prescribe spatially and temporally varying grazing pressure on A. fundyense, we parameterize the impact of grazing with a constant specific loss rate m (day -1 ).…”
Section: Population Dynamics Modelmentioning
confidence: 99%
“…Studies on the effects of PST-containing prey on consumers have shown variable results (Turner & Tester 1997) ranging from non-detectable in some copepods (Colin & Dam 2003) to decreased feeding (Teegarden 1999), decreased fecundity (Guisande et al 2002a), delayed development (Frangopulos et al 2000) and direct mortality in others (Colin & Dam 2003). Furthermore, the copepods Calanus finmarchicus (Turriff et al 1995), Eurytemora herdmanii and Acartia tonsa, as well as the barnacle Semibalanus balanoides (Teegarden 1999;Teegarden et al 2001) have been shown to avoid feeding on PST-containing prey when offered together with a nontoxic food option.…”
Section: Introductionmentioning
confidence: 99%